CRISIS: RECOVERY WITH HIGHER UNEMPLOYMENT AND INFORMALITY - Herrera García, Beatriz (2010)
The deepening of the global world crisis charged a heavy toll on employment worlwide. A rapid rise in the unemployment has been witnessed since 2008 and is expected to worsen in 2009 and 2010. The proyections put the rise in unemployment (flow) at 61 million over in 2009, also rise higher unemployment stock at 240 million, but as the situation continues to deteriorate this number will be historical highdest unemployment, source OIT. Probably higher unemployment rates may persist for some time. Lessons from past world crisis indicate that it typically takes four or five years for unemployment rates to return to pre-crisis levels after economic recovery has set in. This is because massive rises in log-term unemployment and greater labour market informalization are very difficult to reverse. If these trends take root, the negative effects of the crisis will be long-lasting.